Improving mental health in high school students shortly before their final exams — a pilot study of a stress management intervention - Kortsch, Timo; Wegener, Nico; Schwake, Manon Elisa (Frontiers in Education, 2025)
Stress - exacerbated by the COVID-19 pandemic - has become a major problem for students. Students who are about to graduate, are particularly affected, as they experience significant pressure from their final exams while simultaneously facing far-reaching decisions about their future. Stress management interventions can therefore be a valuable way to foster the development of more effective coping strategies. This study utilized a pre-post follow-up design to examine the effectiveness of the 2 days “Simply Less Stress” intervention - a structured program based on the Demands-Resources framework that encourages students to reflect on their individual stress emergence and equips them with practical stress management strategies - as a large group training in a group of high school graduates (N = 34). In addition, quasi-experimental effects on efficacy were examined in students who were undergoing parallel psychological supervision (or not). The results showed that the intervention significantly (p < 0.05) reduced burnout symptoms (dimension reduced feeling of efficacy: η2partial = 0.523) and increased overall study engagement (η2partial = 0.606). The exploratory analyses revealed that students currently receiving psychological support also benefited from the course, experiencing a significant increase in wellbeing. The results were supported by qualitative data from the questionnaires. This pilot study contributes to existing literature by providing preliminary evidence that a stress management intervention can achieve positive outcomes for students with and without parallel psychological support. The findings of this study emphasize the importance of implementing effective interventions, especially during particularly stressful episodes, to address stress among high school students and foster their wellbeing.